The incidental vocabulary acquisition and content comprehension among ESL learners through subtitling of English movies : a case study - Athirah binti Mortada (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The primary aim of this research is to identify if ESL learners can acquire incidental vocabulary by using subtitles in English movies. The study is also interested in identifying the ESL learners' comprehension of the content of movie through English subtitles. It also seeks to identify the ESL learners' attitudes towards watching subtitled movies as an acquiring tool. While many studies have proven the effectiveness of using subtitles in learning English, there is a still a lack of research that focus on the modality of subtitling which results in the optimum vocabulary acquisition and on content comprehension among ESL learners. Most studies tend to focus on the listening comprehension of EFL learners. A mixed-method of qualitative and quantitative were utilized for this study where a time series-design was employed which involves the pre-test, movies viewing the Harry Potter series with bimodal subtitle. Both pre-test and post-test as well as interview sessions were conducted as part of data collection. The difference in the scores between the pre-test and the post-test indicates that there is a significant increase in the participants' vocabulary level. As for content comprehension, a significant number of students had responded to the interview questions with correct answers and this is a reflection of the participants' comprehension of the content of the movie. Findings from this study can be used to enhance theoretical knowledge in the area of English language acquisition and learning. Both learners and educators can benefit from this research in terms of implementing the use of movies and subtitles in the teaching of English Language. The analysis and discussions from the study provide a platform for curriculum designers to polish and further improve on their courses.